Design and Characteristic Research of the Spindle Box of Vertical Machining Center - Gao Dongqiang; Yang Lei; Sun Qian; Zhang Xifeng (Jixie chuandong)
Headstock is the key components of the high speed vertical machining center,its static stiffness,dynamic characteristics has great effect on machining precision and stability of machining center.Taking DVG850 high speed vertical machining center spindle box as the research object,the design scheme of geometrical model of four kinds of different structure of spindle box is established,by using the finite element simulation software,the simulating calculation of the statics,modal and harmonic response of the spindle box are carried out,the resonance region of spindle box under static stiffness,natural frequency,vibration mode and the excitation frequency are got.Through the comparison analysis of finite element simulation of cloud and data,known that scheme two rib structure is the best layout,it is indicated that the research method can be to improve the spindle box structure natural frequency and increase the structure stiffness.provides the basis for avoiding resonance,for other machine tool spindle box the theory basis for optimization of structural design and improvement is provided,the design cycle can be shorten.